STRUKTUR KOMUNITAS TERIPANG (HOLOTHUROIDEA) DI KAWASAN PANTAI DESA ONDONG KECAMATAN SIAU BARAT KABUPATEN SIAU TAGULANDANG BIARO1 - Syafludin Lagio; Lawrence J.L. Lumingas; Gaspar D. Manu (Sam Ratulangi University, 2014)
Sea cucumbers is a group of marine invertebrates belonging to class holothuroidea. At this time, the hunting for sea cucumber is not just targetted on the expensive species, but also the cheap one. The exploitation pressure has caused population decline which can cause changes in their community structure. This research was aimed to understand the types of sea cucumber, analyze the structure of the community sea cucumber which includes the density of individuals, diversity index, the dominance index, interspecific and the dispersion pattern. Sample collection was done at night at the lowest tide in December, 2013. Based on the research activities in the coastal areas of Ondong, west Siau district, Siau-Tagulandang-Biaro regency, 7 species of holothuroidea were found : Holothuria atra, Holothuria leucospilota, Actinopyga echinites, Actinopyga lecanora, Bohadschia argus, Bohadschia marmorata and bohadschia vitiensis, respectively with mean individual density of 0.797 ind/m2, diversity index (H’ = 1.718), equity index or harmony (e = 0. 883), dominance index (C = 0.218), interspecific association between 7 species forming 5 pairs of positive associations and 16 pairs of negative association andrandomdistribution. Keywords : Structure communities, sea cucumber, Ondong, Sitaro ABSTRAK Teripangadalah sekelompokinvertebrata lautyang termasuk dalam kelasHolothuroidea. Pada saat ini, perburuanuntukteripangtidak hanyaditargetkanpada spesiesmahal, tetapi jugayang murah. Tekananeksploitasitelah menyebabkanpenurunan populasiyang dapat menyebabkanperubahan pada strukturkomunitasnya. Penelitian inibertujuan untukmemahami jenisteripang, menganalisisstrukturteripangyang meliputikepadatanindividu, indeks keanekaragaman, indeksdominasi, asosiasi antar spesies danpola penyebaran. Pengambilan sampeldilakukanpada malam harisaat surut terendahpada bulan Desember2013.Berdasarkankegiatan penelitiandiwilayah pesisirOndong, kecamatan SiaubaratKabupatenSiau-Tagulandang-Biaro, ditemukan 7spesiesteripang : Holothuriaatra, Holothurialeucospilota, Actinopygaechinites, Actinopygalecanora, Bohadschiaargus, Bohadschiamarmoratadanbohadschiavitiensis,masing-masing dengankepadatan individurata-rata0.797ind/m, indeks keanekaragaman(H' = 1.718), indekskemerataan atau keserasian(e = 0.883), indeksdominansi(C = 0.218), asosiasiantar 7spesiesmembentuk5pasangasosiasipositif dan16pasangasosiasinegatif danpenyebaran acak. Kata kunci : Struktur komunitas, teripang, Ondong, Sitaro 1Bagian dari skripsi 2Mahasiswa Program Studi Manajemen Sumberdaya Perairan FPIK-UNSRAT 3Staf pengajar Fakultas Perikanan dan Ilmu Kelautan Universitas Sam Ratulangi